Peningkatan Pendapatan Restoran dengan Promosi Makanan dan Minuman di Town Hall Restoran, Midtown Hotel Samarinda - Suwarno, Supriyadi Hadi; Supriyadi, Adhi (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the effect of five food and beverage promotion strategies, price, product, experiential, loyalty, and digital promotions on increasing restaurant revenue, considering the moderating role of seasonality, customer demographics, and service quality. The study was conducted at the Town Hall Restaurant, Midtown Hotel Samarinda, using a quantitative approach with an explanatory design. Data were collected through closed questionnaires distributed to 300 customers and semi-structured interviews with seven key informants from the restaurant management. The analysis techniques used include multiple regression, moderated regression, and Importance Performance Analysis (IPA). The results showed that all promotional strategies had a significant effect on revenue, with digital promotion having the most dominant effect. Moderator variables were also shown to strengthen the indirect effect of promotional strategies on revenue. IPA findings revealed a large performance gap in the digital and personalization aspects, although both factors were considered very important by customers. In conclusion, an integrated and contextual promotional strategy is needed to maximize restaurant revenue. It is recommended that management focus on optimizing digital promotions and application-based reward systems, and adjusting the promotional approach to customer profiles and operational dynamics. Keywords: F&B promotion strategy, seasonality, customer demographics, service quality